TRANSCATHETER AORTIC - VALVE IMPLANTATION (TAVI) – AN EXPERIENCE AT ARMED FORCES INSTITUTE OF CARDIOLOGY - Siddiqui, Abdul Hameed; Aziz, Sohail; Maken, Ghulam Rasool; Khan, Ali Nawaz; Tuyyab, Farhan; Saif, Mohsin; Iqbal, Tahir; Kamran, Javeria; Janjua, Anam Fatima; Ahmed, Imran (Pakistan Armed Forces Medical Journal, 2019)
Objective: To share our experience of percutaneous trans-catheter aortic valve implantation TAVI in patients with severe symptomatic aortic stenosis.Study Design: A retrospective cross sectional study.Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases (AFIC/NIHD) Rawalpindi, from Mar 2015 to Aug 2019.Methodology: Sixteen patients have undergone transcatheter aortic valve implantation since 2015 in the institute. Base line blood chemistry including creatinine clearance, ultrasonography abdomen, carotid Doppler, CXR, HRCT chest was done in all cases as part of the protocol. All patients under went procedure through trans-femoral route. Valve structure and peripheral vasculature for suitability of the procedure was assessed by computerized coronary tomographic angiography (CCTA) with TAVI protocol. Procedure was carried out under general anesthesia in all patients except one.Results: Sixteen patients underwent the procedure successfully with reduction of the mean gradients immediately after valve implantation to less than 15mmHg recorded in the cath lab angiographically sub-sequently complemented by echocardiography. There were 2 deaths during the index hospitalization. Both occurred in the cath lab, one death was due to development of severe acute aortic regurgitation and second was due to acute coronary obstruction. Four patients died in next three months during follow up. One patient required permanent pacemaker because of development of left bundle branch block and second degree atrio-ventricular (AV) block post procedure.Conclusion: Transcatheter aortic valve implantation in patients with severe symptomatic aortic stenosis is a very effective and safe procedure and reasonable alternative to surgical valve replacement in high operative risk individuals.